Drosophila Pur-? binds to trinucleotide-repeat containing cellular RNAs and translocates to the early oocyte. - Aumiller, V.; Graebsch, A.; Kremmer, E.; Niessing, D.; Förstemann, K. (RNA Biology., 2012)
Pur-? was identified as a DNA-binding protein with high affinity for the single-stranded PUR-motif (GGN)n. Bound to DNA, Pur-? can both activate and repress transcription. In addition, Pur-? binds to RNA and may participate in nuclear RNA export as well as transport of cytoplasmic neuronal mRNP granules. The heritable trinucleotide-repeat expansion disease Fragile X associated Tremor and Ataxia Syndrome (FXTAS) leads to interaction of Pur-? with mutant, abnormally long r(CGG)n stretches, which appears to titrate the protein away from its physiologic mRNA targets into nuclear RNA-protein aggregates. We examined the function of Drosophila Pur-? and demonstrate that the protein accumulates in the growing oocyte early in oogenesis. Co-purifying proteins reveal that Pur-? is part of transported mRNP complexes, analogous to its reported role in nerve cells. We analyzed the subcellular localization of mutant GFP-Pur-? fusion proteins where either nucleic acid binding or dimerization, or both, were prevented. We propose that association with mRNAs occurs in the nucleus and is required for nuclear export of the complex. Furthermore, efficient translocation into the oocyte also requires RNA binding as well as dimerization. RNA binding assays demonstrate that recombinant Drosophila Pur-? can bind r(CGG) 4 with higher affinity than previously thought. Related sequences, such as r(CAG) 4 and the consensus sequence of the opa-repeat r(CAG) 3CAA, can also associate with Pur-? in vitro and in vivo. The mRNA target spectrum of Pur-? may therefore be larger than previously anticipated.